2014
DOI: 10.1242/jeb.099929
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory neuron AWC promotes avoidance to normally palatable food following chronic dietary restriction

Abstract: Changes in metabolic state alter foraging behavior and food preference in animals. Here, I show that normally attractive food becomes repulsive to Caenorhabditis elegans if animals are chronically undernourished as a result of alimentary tract defects. This behavioral plasticity is achieved in two ways: increased food leaving and induction of aversive behavior towards food. A particularly strong food avoider is defective in the chitin synthase that makes the pharyngeal lining. Food avoidance induced by underfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 66 publications
(84 reference statements)
1
20
0
Order By: Relevance
“…It has also been found that both arrested L1 or dauer larvae, which are C. elegans life stages generated under starvation conditions, produce signals that trigger adult food-leaving 16 or dispersal. This is reinforced by evidence that population density can trigger dispersal for wild-type 14 and it is also enhanced in a chitin synthase mutant, chs-2 , which is nutritionally compromised 9 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has also been found that both arrested L1 or dauer larvae, which are C. elegans life stages generated under starvation conditions, produce signals that trigger adult food-leaving 16 or dispersal. This is reinforced by evidence that population density can trigger dispersal for wild-type 14 and it is also enhanced in a chitin synthase mutant, chs-2 , which is nutritionally compromised 9 .…”
Section: Introductionmentioning
confidence: 92%
“…Various factors modulate the interaction of C. elegans with a food lawn: Pathogenic bacteria 4 , 7 , 8 , RNAi targeted to essential cellular processes 1 and exposure to a range of chemical toxins 1 all promote food-leaving. Worms fed on hard to digest bacteria 4 or with an impaired ability to feed and digest bacteria 9 also show enhanced food-leaving which has been interpreted as an indication of nutritional cues that regulate the behaviour 9 . The levels of metabolically important gases affects food-leaving with high carbon dioxide 10 and oxygen levels 11 causing worms to leave a food patch, the suggestion being that the animals integrate their response based on the benefits of feeding versus the danger of potentially toxic ambient air conditions 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, eat-2 mutants show an enhanced probability of leaving a food patch relative to N2 Olofsson 2014). Due to the pumping defect of eat-2 mutants, it is possible the higher leaving probability on low-quality food is due to the lower feeding rate of the mutant as less nutrient is ingested from the environmentIn this context it is interesting to note C. elegans mutants that are chronically undernourished due to alimentary tract defects will also leave a food patch more readily and even show avoidance of bacteria that are otherwise attractive to wild-type animals (Olofsson 2014).This makes a case for coupling between feeding or nutritional intake and the locomotory circuits and has provided an interesting route to investigating 'decision-making' behaviour of the worm in the relation to its food environment (Milward et al 2011). (Olofsson 2014)…”
Section: Acetylcholine and Food-related Locomotion Behavioursmentioning
confidence: 99%
“…Whilst at first sight this seems a simple repertoire of behaviours, C. elegans, just like more complex animals, makes elaborate decisions in the context of feeding (Busch and Olofsson 2012). For example, their feeding behaviour is influenced by their nutritional state (Olofsson 2014) and they can learn to avoid pathogenic bacteria (Zhang et al 2005). Intriguingly, males unlike hermaphrodites will abandon food to find a mate (Ryan et al 2014;Lipton et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To examine whether TAX-2/TAX-4 function in these neurons to modulate the avoidance behavior, we performed cell-specific rescue experiments with tax-4 by expressing tax-4 cDNA under various promoters in tax-4(p678) mutants. tax-4 mutants in which tax-4 is rescued in the ASI neurons either through the srbc-65 promoter or the str-3 promoter (Beverly et al 2011;Olofsson 2014) showed significantly higher avoidance of the worm extract than the mutants without rescue ( Figure 4F). Similar effects were achieved by restoring tax-4 in the ASK neurons ( Figure 4F).…”
Section: Worm Extract Avoidance Requires the Asi And Ask Neuronsmentioning
confidence: 99%